2007
DOI: 10.1007/s00432-007-0204-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the impact of 3- versus 8-month neoadjuvant hormonal therapy on outcome of laparoscopic radical prostatectomy

Abstract: The prolonged NHT (8-month) did not affect the operative or postoperative parameters. The LRP can be safely performed in patients after prolonged NHT. Prospective randomized studies are required to determine whether prolonged NHT reduces the risk of biochemical recurrence after LRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 27 publications
1
29
2
Order By: Relevance
“…Drains were removed in all patients before discharge. Catheters were removed after a mean (range) of 6.1 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) days, all with no previous cystogram. Twenty-nine patients had a modified pelvic lymphadenectomy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Drains were removed in all patients before discharge. Catheters were removed after a mean (range) of 6.1 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) days, all with no previous cystogram. Twenty-nine patients had a modified pelvic lymphadenectomy.…”
Section: Resultsmentioning
confidence: 99%
“…LRP was performed using the Montsouris technique, with some modifications by us [10][11][12][13]. In brief, after the puboprostatic space is developed, the bilateral endopelvic fascia of the prostate is dissected longitudinally toward the apex and puboprostatic ligament section.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been regarded as a good choice for localized prostate cancer in China (Pu et al 2007). Since the transperitoneal LRP was Wrst performed (Schuessler et al 1992), until 6 years later, Guillonneau et al (1998) reported an initial series of 28 cases with a standardized technique based on the primary access to the seminal vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Time to continence recovery was signiWcantly shortened in LRP. Based on Steiner's technical considerations and our previous experience (Pu et al 2007;Steiner 2000aSteiner , 2000bSteiner , 2000c), we conducted a simple apical dissection of the prostate in LRP. In this study, we described the modiWed technique in LRP and evaluated the early recovery of urinary continence.…”
Section: Introductionmentioning
confidence: 99%